Adopción de tecnologías para el impulso de la producción de maíz en el cantón Arenillas - Huailas Feijoo, Andrey Guiberto (2010)
We analyzed the degree of adoption of technologies that took place in parishes Arenillas, Acreages, Palmales and Carcabón, El Oro province has a dry tropical climate with a temperature of 25,10 oC and rainfall of 658 mm. The objectives were: 1. Identifying the adoption of technology that pushed corn production. 2. Establish the existing techniques that are more appropriate for corn producers in the canton Arenillas. 3. To determine the socio-economic aspects that limit or favor the use of technologies. We surveyed 143 farmers in the canton, to the outcome groups was made regarding the extent of each farm, thus established the following conclusions: With regard to crop management Arenillas canton producers, 71.5% had personal experience based on their ancestors and exchange of experiences among farmers, 100% using planting system directly, 84,75% performed sowing between the months of January to June because many producers take advantage of these dates for the rainy season, where 93% of producers use certified seeds on their plantations. As to whether they have received technical advice, 24.5% of farmers have received at least once technical advice by the MAGAP. Also keep a tight control for plant protection and weed problems, taking the 56,75% of farmers maiceros applications made chemicals on their crops from experience.